Odpowiedzi

2009-10-07T17:12:21+02:00
-18+(-11+9,5)=-18+1,5=-16,5

(-63+28)-(-16-13)=-35-(-29)=-35+29=-6


nie wiem czy dobrze...
Najlepsza Odpowiedź!
2009-10-07T17:12:26+02:00
Zadanie 1
Do liczby -18 dodaj różnicę liczby -11 i liczby -9,5

-18 + (-11 -(-9,5))= -18 + ( -11 + 9,5 ) = -18 - 1,5 = -19.5


Zadanie 2
Do sumy liczb -63 i 28 odejmij sumę licz -16 i -13

(-63 + 28) - ( -16 +(-13)) = -35 -(-16 -13) = -35 + 29 = -6
1 5 1
2009-10-07T17:12:44+02:00
Zadanie 1
Do liczby -18 dodaj różnicę liczby -11 i liczby -9,5
-11-(-9,5)=-11+9,5=-1,5
-18+(-1,5)=-19,5
Zadanie 2
Do sumy liczb -63 i 28 odejmij sumę licz -16 i -13
-63+28=-35
-16+(-13)=-16-13=-29
-35+(-29)=-35-29=-64